Stop! I am Shaking: Workplace Aggression and Anxiety among Interns in Klang Valley - Mohamad Besir, Mohamad Shahril; Abdullah, Mohd. Zulkifli; Saadun, Saadiah Juliana; Mohd. Tobi, Siti Noraini; Mat Hasan, Nor Zaihan; Huzahim, Ayman Hazim (Information Management and Business Review, 2023)
Internships have become crucial to help students make them stand out while at the same time providing training and work experience for the students. However, the issue of workplace aggression among internship students is increasing and is worrying many parties as it is a prevalent matter that internship students can be subjected to mistreatment in the workplace. Drawing from the Job Demand-Resource model and Conservation of Resources theory, this paper sought to identify the relationship between independent variables such as workplace bullying, interpersonal conflict, abusive supervision and anxiety among interns from the Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam campus who underwent internship in Klang Valley. An online questionnaire was distributed to the interns, and 128 completed sets were responded to. The results found that there were positive correlations between workplace bullying, abusive supervision and interpersonal conflict on anxiety among the interns. The findings suggest that aggression in the workplace correlates with psychological disorders as it can cause the interns to experience psychological strain such as anxiety. In general, the research aims to contribute to a better understanding of workplace aggression and anxiety to mitigate these conundrums and foster a positive and supportive atmosphere for internship students. Furthermore, both organizations and interns need to have the knowledge and skills to prevent them from experiencing psychological illnesses. The implications of the study will be further discussed in the paper.